2002
DOI: 10.1161/01.cir.0000032918.33237.04
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Growth Factor Enhances Post-Pneumonectomy Lung Growth by Alveolar Proliferation

Abstract: Background Keratinocyte growth factor (KGF) has been shown to play an important role in pneumocyte proliferation and lung development. We hypothesized that exogenous KGF would enhance postpneumonectomy compensatory lung growth through alveolar proliferation. Methods and Results Adult Sprague–Dawley rats were used. Left pneumonectomy was performed in group P, sham thoracotomy in group S, and left pneumonectomy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We could also induce the distal airway SSCs stemness by supplementing the essential stem cell growth factors and cytokines, whose availabilities are greatly reduced in chronic lung diseases. Exogeneous FGF7 (also known as keratinocyte growth factor) application could promote compensatory lung growth by alveolar proliferation post PNX in mice 108 . A randomized controlled phase-I clinic trial showed that intravenous application of FGF7 attenuated alveolar injury in patients with acute respiratory disease syndrome (ARDS) 109 .…”
Section: Therapeutic Strategies For Distal Airway Repair In Chronic L...mentioning
confidence: 99%
“…We could also induce the distal airway SSCs stemness by supplementing the essential stem cell growth factors and cytokines, whose availabilities are greatly reduced in chronic lung diseases. Exogeneous FGF7 (also known as keratinocyte growth factor) application could promote compensatory lung growth by alveolar proliferation post PNX in mice 108 . A randomized controlled phase-I clinic trial showed that intravenous application of FGF7 attenuated alveolar injury in patients with acute respiratory disease syndrome (ARDS) 109 .…”
Section: Therapeutic Strategies For Distal Airway Repair In Chronic L...mentioning
confidence: 99%
“…Lung epithelial regeneration has been improved in animal studies using both biopharmaceuticals and small molecule approaches. Biopharmaceutical approaches shown to increase epithelial cell proliferation after lung injury have included keratinocyte growth factor (KGF, Kaza et al, 2002 ; HGF, Dohi et al, 2000 ) and vascular endothelial growth factor (VEGF, Kunig et al, 2005 ). The small molecule LDN-193189 – a BMP antagonist – promoted basal cell proliferation during airway injury ( Tadokoro et al, 2016 ), while amlexanox – a Wnt-activator – was identified in a drug repurposing study and promoted repair in the elastase-induced emphysema mouse model ( Costa et al, 2021 ).…”
Section: Promoting Lung Regeneration By Endogenous Stem Cellsmentioning
confidence: 99%